Herpesviruses in Captive Chelonians in Europe Between 2016 and 2020 - Leineweber, Christoph; Müller, Elisabeth; Marschang, Rachel E. (Frontiers in Veterinary Science, 2021)
Herpesviruses are important pathogens in tortoises and turtles, yet little is known about the epidemiology of these viruses. We analysed herpesviruses detected by PCR in samples from captive chelonians in Europe according to virus strain, host species, year and season in which the animal was tested, and country in which the animal was kept. A total of 4797 samples submitted to a diagnostic laboratory in Europe between January 2016 and December 2020 were evaluated. Of these, 312 (6.50%) were positive for herpesviruses. The types most commonly found were testudinid herpesvirus (TeHV)1 (143 positive, 45.83%) and TeHV3 (153 positive, 49.04%), but also included TeHV2 (1 positive, 0.32%), TeHV4 (3 positive, 0.96%), Terrapene herpesvirus 1 (7 positive, 2.24%), Trachemys herpesvirus 1 (2 positive, 0.64%), and three previously undescribed herpesviruses (0.96%). Herpesviruses were detected in chelonians in the families Testudinidae, Emydidae, Geoemydidae, and in the suborder Pleurodira. Among the species for which 100 samples or more were available, the highest proportions of positive samples (positivity rates) were found in samples from Horsfield’s tortoises (Testudo horsfieldii) (14.96%), and radiated tortoises (Astrochelys radiata) (14.05%). Among tortoises (Testudinidae), viruses were most often detected in the spring, while in emydid turtles (Emydidae) they were most often detected in the summer. A comparison of the positivity rates according to country showed significant differences, with the highest rate in samples from Italy (16.01%). This study showed clearindicated possible differences in herpesvirus detection positivity rates depending on host species, virus strain, year of sampling, season, and country of origin. It provides useful information in further understanding fluctuations in infection rates as well as in helping to guide decision making for herpesvirus diagnostics in chelonian patients. It also provides evidence for the international dispersal of herpesviruses with their hosts through international trade.